Meta Analysis: Correlations between Age at Menarche, Parity, and Hormonal Contraceptive Use with Breast Cancer in Women of Reproductive Age (Journal of Maternal and Child Health, 2024)
Background: Breast cancer is the most common cancer and the leading cause of cancer death in women worldwide. The implementation of the program in reducing the incidence of breast cancer is focused on prevention based on evidence of risk factors. This study aims to estimate factors that influence the incidence of breast cancer in women of productive age.Subjects and Method: This study used systematic review and meta-analysis using PICO. Population: Women of productive age. Interventions: menstruation at ≥13years, parity (multipara) and using hormonal contraceptives. Comparison: menstruation at
Keywords: risk factors; menarche; parity; breast cancer